Analisis Nilai Karakter Mandiri dan Gotong Royong Anak Komunitas Cahaya Bunda - Rossabela Rindiyanto; Badruli Martati; Deni Adi Putra (Universitas Indraprasta PGRI Jakarta, 2023)
Cahaya Bunda Community is a non-formal school established to assist street children on the banks of the Kalimas Red Bridge River who do not attend school or who have been dropped out of school to get more positive learning activities. This research aims to analyse the value of independent character and mutual assistance in the Cahaya Bunda Community. The research method used was descriptive qualitative with a case study approach. Data collection techniques in this study used triangulation techniques, namely: observation, interviews, and documentation and data analysis in research using data reduction, data presentation, and conclusions. The results of the research that has been carried out can be concluded that the main values of independent character and mutual assistance in the Cahaya Bunda Community have run very well in the independent character of children, including hard work in learning seriously, creatively having initiative in learning, courage in expressing opinions, and responsibility in self-discipline while learning. In the character of mutual assistance, children can cooperate in group discussions, solidarity, love to help fellow friends, and respect the opinions of others. It can be concluded that the value analysis of independent character and mutual assistance of children of the Cahaya Bunda Community has been fully carried out well.